Intermittent Chest Pain - Erin Schlossman; Megan Taylor; David Masneri (Association of American Medical Colleges, 2016)
Abstract Introduction Deep T inversions in the anterior leads (Wellens' syndrome) are a sign of life-threatening coronary artery occlusion. The purpose of this simulation experience is to present a Wellens' syndrome case that allows medical students, emergency medicine residents, and emergency medical service providers to test their knowledge base and critically evaluate the management of the following type of acute coronary syndrome: a Wellens' syndrome (deep T wave inversions in anterior leads) that develops into a ST-elevation myocardial infarction (STEMI) during management. Methods The module contains four elements to help direct the simulation experience. The first element is the case narrative, which includes all pertinent case information, interpretations of the case information, and anticipated case branch points. The second element is a PowerPoint presentation that contains pertinent case lab information, X-ray, and ECGs to be used during the case simulation. The third element is a PowerPoint presentation that contains teaching points for the debriefing session. Finally, an evaluation form is included containing recommended actions. Results A pilot simulation was performed with emergency medicine residents. Residents felt the case emphasized the importance of patient reevaluation, comparing new and old ECGs, and obtaining new ECGs with changes in clinical status. Discussion The case was effective in familiarization and teaching about Wellens' Syndrome. Additionally, most of the participants identified a general lack of comfort in recognizing Wellens' ECG changes (even when the management decisions were correct), secondary to lack of familiarity. In this regard, the case was received well as it is an opportunity to critically review and discuss the Wellens' phenomenon.